Facilitating conditions for farmer learning behaviour in the student-to-farmer university outreach - Kalule, S.W.; Sseguya, H.; Ongeng, D.; Karubanga, G. (Informa UK Limited, 2019)
Purpose: This study elucidates on how faculty supervision support to students during farm placements and other facilitating conditions influence farmer learning in the student-centred university outreach.